Pendidikan Kristen Transformatif dalam Keluarga - Jacob Mesakh (STIPAK Malang, 2020)
The dynamics of family life connected with education or care reflect ongoing education for family members. The pedagogical aspect of life renewed from within has been clearly stated to Nicodemus and the Samaritan woman but also to Israel. The last centered on God's law and the first on the person of Christ. By looking at this reality and development, the theological basis of transformative education itself in the present level is centered on Christ (Christocentric) so that students experience the abundance of Christ's grace and truth through His Spirit (Holy Spirit) who is ready to renew the individual's mind. The call to be a light in this world begins with the examination and light of Christ in the minds of students or children of believers' families. AbstrakDinamika kehidupan kekuarga terhubung dengan pendidikan dan atau pengasuhan mencerminkan sedang berlangsungnya pendidikan bagi anggota keluarga. Aspek pedagogik dari kehidupan yang dibarui dari dalam telah dinyatakan dengan jelas kepada Nikodemus dan perempuan Samaria tetapi juga kepada bagsa Israel. Yang terakhir berpusat kepada hukum Allah dan yang awal kepada Pribadi Kristus. Dengan melihat kepada kenyataan dan perkembangan ini, maka basis teologis dari pendidikan transformatif itu sendiri dalam aras kekinian berpusat kepada Kristus (Kristosentris) agar peserta didik mengalami kelimpahan kasih karunia dan kebenaran Kristus melalui Roh-Nya (Roh Kudus) yang siap sedia membarui batin individu. Panggilan untuk menjadi terang di dunia ini diawali dengan perujudan terang Kristus di dalam batin peserta didik atau anak-anak keluarga orang percaya.